Investigation on the behavior of wastewater from industrial cooling water systems - Aatiq Aftini, Ab Rahman (2009)
Industrial wastewater is discharged from industries and associated processes utilizing water. Industrial water cooling systems generated large amount wastewater. Industrial water cooling systems produce waste such as silt, heat, biocide and slimes. The problems need to be controlled or eliminated are at interferes with heat, commonly referred to as deposits and deterioration of the water-contacted equipment, referred to as corrosion. Therefore, this research is carried out to overcome this problem by determine the behavior of wastewater from industrial water cooling systems and determine the influence of concentration of Acid Hydrochloric in water cooling systems during Passivation process. The parameters considered based on APHA method in Standard Methods for Examination of Water and Wastewater (2005) are including Chemical Oxygen Demand (COD), Total Organic Carbon (TOC), pH, Turbidity, Heavy Metals (Iron, Lead, Copper, Nitrate and Nickel). The study of behavior of wastewater from industrial water cooling systems will be taken place at behind the block W, Universiti Malaysia Pahang, Campus Gambang, Pahang Darul Makmur. The results show that all parameters except lead are recorded to be over than standard that have been use for comparison purpose such as the highest concentration of iron recorded that 3012 mg/L but the standard is 5 mg/L. As a conclusion, this effluent need proper treatment before been discharge because majority of parameters over than standard propose. According to study of concentration of Acid Hydrochloric (HCl) can affect the efficiency of passivation for Carbon Steel pipe. For concentration HCl 2 %, passivator needs to increase from 0.1% to 1.0% and pH also not exceed to alkali conditions or not in range 10-12 for effective passivation.